On ?-statistical boundedness of order ? of sequences of fuzzy numbers - Altinok, Hifsi; Et, Mikail (Springer, 2015)
In this paper, we introduce and examine the concept of lambda-statistical boundedness of order beta of sequences of fuzzy numbers and give some relations between statistical boundedness and lambda-statistical boundedness of order beta.
Keywords: Fuzzy number; Statistical boundedness; Statistical convergence